Multimodal composing as a learning activity in English classrooms: Inquiring into the sources of its motivational capacity. (July 2016) - Jiang, Lianjiang; Luk, Jasmine
Abstract: Although multimodal composing (MC) has received growing attention in the field of language education as a textual and literacy practice with significant potential to make learning engaging and motivating, the sources of its motivational capacity as an activity for English learning remain largely unexplored in empirical studies. This paper reports on a study that investigated the experiences and perceptions of 21 students and 5 teachers who participated in a year-long research that engaged students with multimodal composing of video essays in an undergraduate English curriculum in China. Data for this paper were gathered through in-depth semi-structured interviews and written reflections to examine learners' and teachers' perspectives on what makes English learning with MC engaging and motivating. The findings reveal that the motivational capacity of MC derives from seven factors that students experienced during the MC process: challenge, curiosity, control, fantasy, competition, cooperation, and recognition. These findings are helpful in informing our understanding of the motivating features of using multimodal text construction as a learning activity in the language classrooms. They also offer implications on how MC can be used to construct a motivating learning environment for contemporary English learners.